Diversity and floristic enrichment with montane cloud forest species, in an urban forest in Chiapas, Mexico - Bárbara Cruz-Salazar (Madera y Bosques, 2020)
The mountain mesophilic forests (MCF) occupy only between 0.5% and 1% of the Mexican territory and are seriously threatened due to the high rate of deforestation. To contribute to the conservation of tree species of MCF, the present study carried out the objectives of (1) determining the diversity of trees in the urban forest El Cerrito de San Cristóbal, Chiapas, Mexico, (2) floristically enriching the urban forest El Cerrito de San Cristóbal with the plantation of native species of MCF of Chiapas, and (3) describe the genetic diversity introduced through floristic enrichment. The structure and composition of the tree community was recorded through 1000 m2 circular sampling plots, while herbaceous species were recorded in walks along tracks. Fourteen MCF native species were first planted in El Cerrito; then, the introduced genetic diversity was determined using chloroplast DNA PCR-RFLPs (tRNL). A composition dominated by species previously introduced 40 years ago (Cupressus lusitanica, Eucalyptus camaldulensis, and Pinus pseudostrobus) was detected. No recruitment of seedlings and juveniles of canopy trees was observed, and some naturally established individuals of native species were spotted. The genetic diversity introduced was low by species, but for the whole forest it was moderate. The low genetic diversity by species is likely associated with the use of a conservative marker. Urban forests constitute an approach for the conservation of native tree species and their genetic diversity, while promoting the regeneration and diversification of urban forest. This study contributes to the conservation and genetic knowledge of tree species characteristic of montane forests in Mexico.